Wheat Variety-Specific Response to Seeding Rate Under Intensive Management Conditions in Western Kansas in 2019–2020 - R. P. Lollato; B. R. Jaenisch (Kansas Agricultural Experiment Station Research Reports, 2021)
Wheat response to seeding rate is variable and depends on resource availability during the growing season (e.g., fertility, moisture, and temperature). Our objective was to evaluate winter wheat population and grain yield responses to seeding rate and its interaction with variety in a highly-managed production system where manageable stresses were limited. One experiment evaluating the response of the wheat varieties Joe, WB-Grainfield, Langin, and LCS Revere to seeding rates ranging from 200,000 to 1,000,000 seeds per acre was established in a field managed by growers that consistently win state and national wheat yield contests near Leoti, KS. The trials were established on September 25, 2019, after a long fallow. The growing season was extremely dry, with only 6.3 inches of cumulative precipitation (corresponding only to 15% of atmospheric water demand). Stand count increased with increases in seeding rate but final population was closer to the target under low populations. Varieties differed statistically in grain yield but all varieties responded similarly to seeding rate. The lowest yield was recorded across varieties in the treatment with 200,000 seeds/a, with the treatments ranging from 400,000 to 1,000,000 seeds/a all resulting in the same yield level. The variety WB-Grainfield underperformed the other varieties, likely due to more damage from a spring freeze occurring in April 2020. These results suggest that wheat grain yield responses to seeding rate were not dependent on variety, with optimum seeding rates as low as 400,000 seeds/a. We note that increasing seeding rates past this point led to numerical, but not statistical, increases in yield.
Keywords: wheat; seeding rate; population; yield potential; variety